AKUISISI P.T CARREFOUR INDONESIA TERHADAP P.T ALFARETAILINDO DITINJAU DARI UNDANG-UNDANG NO 5 TAHUN 1999 TENTANG LARANGAN PRATEK MONOPOLI DAN PERSAINGAN USAHA TIDAK SEHAT - , Angga Aldilla Gussman, SH ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Acquisition is an expropriation act of a corporate by other company to develop the corporate business. Acquisition which was carried out by Indonesian Carrefour Inc. Ltd toward Alfa Retailindo Inc. Ltd assessed by KPPU (Komisi Pengawas Persaingan Usaha= the Business Competition Controller Commission) as a monopoly deed and morbidity business competition. For the KPPU decision, Indonesian Carrefour Inc. Ltd brought an objection to the South Jakarta district court, and the adjudication of South Jakarta district court cleaned the accusation of Indonesian Carrefour Inc. Ltd of KPPU. In this case, the main issue is whether acquisition carried out by Indonesian Carrefour Inc. Ltd contrary to UU No. 5 year 1999 about exclusion of Monopoly practice and morbidity business rivalry, and whether adjudication of South Jakarta district court have appropriated to accepted acts, and what acquisition effect for business world in Indonesia. After researching and understanding KPPU investigation on its adjudication, the acquisition carried out by Indonesian Carrefour Inc. Ltd toward Alfa Retailindo Inc. Ltd was break the UU No. 5 year 1999, pasal 17, ayat (1) and pasal 25, looking at the adjudication of this case, can be concluded that the judge was not objective in assessing this case and the adjudication was not correct. The acquisition was carried out by Indonesian Carrefour Inc. Ltd also have negative effect for Carrefour counterâs supplier where the Trading term ever increasing and the supplier is significantly damaged.